A Small Molecule β2 Integrin Agonist Improves Chronic Kidney Allograft Survival by Reducing Leukocyte Recruitment and Accompanying Vasculopathy - Khan, Samia Q.; Guo, Lingling; Cimbaluk, David J.; Elshabrawy, Hatem; Faridi, Mohd Hafeez; Jolly, Meenakshi; George, James F.; Agarwal, Anupam; Gupta, Vineet (Frontiers in Medicine, 2014)
Kidney allograft rejection is associated with infiltration of inflammatory CD11b+ leukocytes. A CD11b agonist leukadherin-1 (LA1) increases leukocyte adhesion, preventing transmigration and tissue recruitment in vivo. Here we test the extent to which LA1 mediated activation of CD11b/CD18 enhances kidney allograft survival in a mouse model of fully MHC-mismatched orthotopic kidney transplantation, where C57BL/6J (H-2b) recipients received kidney allografts from Balb/c mice (H-2d). Isograft control recipients received a kidney from a littermate. Control isograft and allograft recipients were treated daily with cyclosporine (CsA) for 2 weeks, while the test group received CsA therapy and daily LA1 injections during week 1 and alternate days during weeks 2-8. LA1 treatment reduced interstitial leukocyte infiltration in the allograft, reduced neointimal hyperplasia and glomerular damage, and prolonged graft survival from 48.5% (CsA only) to 100% (CsA and LA1) on day 60. Serum creatinine levels showed significantly improved kidney function in LA1 treated mice compared to CsA treated allograft controls (0.52 ± 0.18 mg/dL v/s 0.24 ± 0.07 mg/dL (n=5), respectively). Furthermore, combination therapy reduced macrophage infiltration and increased the frequency of FoxP3+ Tregs in the allograft. These findings indicate a crucial role for CD11b/CD18 in the control of leukocyte migration to the transplanted kidney and identify integrin agonist LA1 as a novel potential therapeutic agent for kidney transplantation.